Hacia una clínica de la escucha: el caso clínico en psicoanálisis (2018)
They study of case in psychoanalysis, is a construction, is a cutting about a point, it isn´t about the original case descriptively realized in its totality, what means that the investigator must take off the theoretical structures understood like construction already stablishe, thought it isn´t like that it will let scape that what surprise and advice the mistake in the Other one, it is necessary don´ take upon oneself a known that working at the way of a prejudice that upset the authenticity of listening (Gallo H., 2012). Therefore the clinic case is to explain bases and not to define a model on the outside of psychoanalysis practice, that´s to say, here it can´t separe the case from the analytic experience and all about it implies, the case is made with the material given by the person, allowing to report about the deposition of the individual. Is like that the present clinic case from psychoanalysis, allow to understand that a case by itself testifies, and is make it in the logical incidence about a saying in the listening device allowing to emerge that from singularity, to come out from the person unconscious. Any clinic intervention about psychoanalytic orientation, must give a step to manifestations from unconscious, as the analysis allows that each person be responsible of that with his enjoy, that is related with he enjoys, that is related with his symptoms, his failed acts, with that isn´t “work”, that is repeated, so that he can try reinvent his social tie.